Віковий розвиток швидкісних здібностей студенток - Сергієнко, В.; Sergiyenko, V. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Розглянуто питання технології тестування й контролю розвитку швидкісних здібностей у процесі фізичного виховання студенток. Завданням роботи стало дослідження вікових змін фізичного розвитку та швидкісних здібностей і їх кореляційних взаємозв’язків у студенток 17–20 років основного навчального від-ділення вищих навчальних закладів. Результати роботи засвідчили погіршення показників розвитку швидкісних здібностей, якщо порівняти показники 17-річних із 20-річними студентками з бігу на 30 м і 50 м, зниження становить 3,2 % і 4,4 %, відповідно, частоти рухів руки – 0,5 %, хвату падаючої палиці – 3,5 %. Отримані середні показники розвитку швидкісних здібностей та їх індексів дадуть можливість розробити за 5- й 12-бальними сигмоподібними шкалами диференційовані нормативи оцінок для студенток 17–20 років. . The issue concerning testing methods and control over velocity capabilities development in the process of female students’ physical training is considered. Investigation of physical development age changes and velocity capabilities of their correlation interconnections, related to 17–20 year-old female students of the major educational department at higher educational establishments has become the task of the research. The results of the research testified drop of velocity development performance, if 17-year-old female students performance gets compared to 20-year-old ones in running the distance of 30 and 50 metres, the drop stands for 3,2 % and 4,4 % correspondingly, the frequencies of hand moves – 0,5 %, the grip of the falling stick – 3,5 %. The received average indicators of velocity capabilities development and their indices will give the opportunity to elaborate differential qualifying standards for assessment of 17–20 years old female students according to 5- and 12-point sigmoid scales.
Age Development of Female Students’ Velocity Capabilities
Keywords: швидкісні здібності; антропометричні показники; тестові випробування; студентки; velocity capabilities; anthropometric indices; testing; female students